2002
DOI: 10.1097/00001665-200209000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Solitary Fibrous Tumor of the Orbit

Abstract: Painless unilateral proptosis is a frequent manifestation of numerous orbital neoplastic and non-neoplastic processes. Various mesenchymal tumors of both fibrohistiocytic and vascular origin are well-described causes. Solitary fibrous tumors (SFTs) are rare spindle-cell neoplasms usually found associated with serosal surfaces, especially the pleura, but they have recently been described in a number of extrapleural sites including the orbit. The authors describe the case of an 18-year-old man who presented with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 18 publications
0
26
0
2
Order By: Relevance
“…Several studies point to the fact that no conclusion of the clinical course can be drawn from the histological findings [39]. There are histologically malignant tumors having both an aggressive as well as benign outcome; on the other hand, histologically benign features are no guarantee of a good outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies point to the fact that no conclusion of the clinical course can be drawn from the histological findings [39]. There are histologically malignant tumors having both an aggressive as well as benign outcome; on the other hand, histologically benign features are no guarantee of a good outcome.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there are up to 50 SFTs of the orbit described [1,4,5,6,8,13,15,16,17,18,19,20,21,26,27,28,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46]. The aim of the present study is to present two cases and to review the current literature.…”
Section: Introductionmentioning
confidence: 95%
“…Solitary fibrous tumor (SFT) is a rare spindle-cell tumor of mesenchymal origin that arises most often in the pleura, but may also occur at other organs, including lung, mediastinum, pericardium, peritoneum, retroperitoneal space, pelvis, adrenal gland, kidney, liver, periosteum, salivary gland, thyroid gland, lacrimal gland, breast, nasopharynx, orbit, urogenital system, skin, meninges and spinal cord 3,10,11,13,14,19,21,24,27,33) . Since the first report of orbital SFT by Westra et al 34) in 1994, fewer than 60 cases of orbital SFTs have been reported to date.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, with the development of immunohistochemical method, the number of reported cases have been increasing 9) . One of the most common symptoms is unilateral painless proptosis, which can be accompanied by visual disturbance, palpable orbital mass, ocular mobility disturbance, hyperglobus or blepharoptosis from the secondary mass effect in the orbit 24) . As a general rule, orbital SFT shows an indolent and nonaggressive clinical course.…”
Section: Introductionmentioning
confidence: 99%
“…The biopsy may show large areas of the tumour containing storiform formations, sarcoma-like areas, fascicular formations, neural type palisades, and hemangiopericytoma-like patterns [6]. Differential diagnosis based on histopathological features includes meningioma, fibrous histiocytoma, schwannoma and hemangiopericytoma.…”
Section: Resultsmentioning
confidence: 99%